SISTEM PAKAR MENDIAGNOSA PENYAKIT PADA BURUNG LOVEBIRD DENGAN METODE FORWARD CHAINING BERBASIS WEB - Manurung, Efran Louis; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2025)
The disease known as avian pox poses a serious threat to Lovebirds and can lead to their death. In some regions, this illness is referred to as "patek." The primary cause of this disease is a virus that, upon infecting a Lovebird, triggers excessive growth in the outer skin layer. This growth results in new tissue that quickly dies, forming warts. If left untreated, these warts can enlarge. The avian pox virus can be transmitted in various ways, including bites from infected mosquitoes, flies, contact with sick birds, and even through contaminated food or water. As a result of this infection, Lovebirds may experience respiratory difficulties and struggle to eat, ultimately leading to death. Therefore, it is crucial to develop a system that can assist Lovebird enthusiasts in preventing and addressing this disease. One potential solution is an expert system that can enhance the ability to diagnose symptoms like a professional.